FORMULATION AND IN VITRO EVALUATION OF CURCUMIN LOADED JACKFRUIT SEED STARCH NANOPARTICLES - NATH, JUNMONI (International Journal of Current Pharmaceutical Research, 2020)
Objectives: To meet the above aim the following objectives are undertaken: (1) Isolation of starch from jackfruit seeds and formulation of curcumin loaded jackfruit seed starch nanoparticles (2) In vitro evaluations of the drug loaded nanoparticles Methods: Jackfruit seed starch nanoparticles were prepared by Nanoprecipitation technique. In this technique, jackfruit seed starch was mixed with curcumin and acetone solution using a magnetic stirrer at 600 rpm. To the above solution, water were added dropwise and stirred at room temperature until acetone was completely vaporized. Nanoparticles were separated by centrifugation at 4000 rpm after 40 min. Results: Particle size of prepared nanoparticle formulations was found to be 371 to 411.72 nm with PDI of 0.148 to 0.356. The maximum % drug entrapment was found to be 57.34 % with formulation F5. In vitro release studies showed sustained release of drug till 12 h. Conclusion: The prepared nanoparticles were evaluated for its particle size, drug entrapment efficiency, in vitro drug release study, and surface morphology studies by scanning electron microscopy. The results of Fourier transform infrared studies of 1:1 physical mixture of drug and excipients confirmed the absence of incompatibility. Thus, the study concludes that curcumin loaded jackfruit seed starch nanoparticles were developed successfully by nanoprecipitation, which is expected to enhance the oral bioavailability of curcumin.